Islam dan Pengaruhnya dalam Ritual Pa’dinging-dinging di Desa Adat Tenro Selayar (Perspektif Sejarah Lisan) - Misbah, Misbahuddin (Rihlah: Jurnal Sejarah dan Kebudayaan, 2019)
This study is a historical research that attempts to re-examine the events that occurred in the past. In this study, the authors used two special methods, documentation and interviews. In addition, the approach used in this study is a multidisciplinary approach; history, sociology, anthropology and psychology. The results of this study concluded that the Paingding-dinging tradition had been around long before Islamization occurred in Selayar. On the other hand, in carrying out the ritual practices, the customs of the of Islam are deeply rooted; like Islamic clothing (the use of skullcap and hijab) as well as prayers which are read in old manuscripts are prayers addressed to Allah, the Almighty, with the accompaniment of praise to the Prophet Muhammad. Penelitian ini merupakan penelitian sejarah yang berusaha menelaah kembali peristiwa yang terjadi pada masa lalu. Dalam penelitian ini, penulis mempergunakan dua metode dokumentasi dan wawancara. Hasil dari penelitian yang dilakukan bahwa keberadaan tradisi Pa’dinging-dinging telah ada jauh sebelum terjadi Islamisasi di Selayar. Di sisi lain, pada pelaksanaan praktek ritual adatnya sendi-sendi ke-Islaman; seperi pakaian Islami (penggunaan kopiah dan hijab) juga do’a yang dibacakan dalam manuskrip tua merupakan do’a yang ditujukan kepada Allah swt dengan iringan pujian kepada Nabi Muhammad saw.